Estimations of the Constants in Inverse Inequalities for Finite Element Functions (Journal of Computational Mathematics, 2018)
In this paper, we estimate the constants in the inverse inequalities for the finite element functions. Furthermore, we obtain the least upper bounds of the constants in inverse inequalities for the low-order finite element functions. Such explicit estimates of the constants can be used as computable error bounds for the finite element method.
Keywords: Inverse inequality; Finite element function; Bound of the constant.